Review article: Fabrication of nanofluidic devices - Duan, Chuanhua; Wang, Wei; Xie, Quan (Biomicrofluidics, 2013)
Thanks to its unique features at the nanoscale, nanofluidics, the study and application of fluid flow in nanochannels/nanopores with at least one characteristic size smaller than 100 nm, has enabled the occurrence of many interesting transport phenomena and has shown great potential in both bio- and energy-related fields. The unprecedented growth of this research field is apparently attributed to the rapid development of micro/nanofabrication techniques. In this review, we summarize recent activities and achievements of nanofabrication for nanofluidic devices, especially those reported in the past four years. Three major nanofabrication strategies, including nanolithography, microelectromechanical system based techniques, and methods using various nanomaterials, are introduced with specific fabrication approaches. Other unconventional fabrication attempts which utilize special polymer properties, various microfabrication failure mechanisms, and macro/microscale machining techniques are also presented. Based on these fabrication techniques, an inclusive guideline for materials and processes selection in the preparation of nanofluidic devices is provided. Finally, technical challenges along with possible opportunities in the present nanofabrication for nanofluidic study are discussed.